Consumer Protection in the E-Cigarette Industry: Legal Responsibility of Business Actors for Non-Compliance with Information Labels and Health Warnings - Herry M Polontoh (Ipso Jure, 2024)
In recent years, the popularity of e-cigarettes has increased rapidly, especially among teenagers and young adults who consider them a safe alternative to tobacco cigarettes. However, these products still contain harmful substances, while many products on the market do not list adequate health warnings. This indicates potential violations of consumer protection and underscores loopholes in legal oversight that allow business actors to ignore these obligations. The lack of clarity of labels and misleading advertisements poses health risks that consumers are not aware of, especially for the younger generation who are vulnerable to these promotions. This study examines the legal responsibility of business actors in fulfilling health labeling obligations in accordance with the Consumer Protection Law and Government Regulations related to addictive substances. With a normative juridical method, this study assesses the regulation of labeling e-cigarette products and the need for stricter policies. The results of the study are expected to provide policy recommendations to improve regulations and increase supervision, so that consumers' rights to health information are fulfilled and the e-cigarette industry is more responsible in prioritizing public health.